Studies on Monstereae (Araceae) of Borneo II: Furtado’s Rhaphidophora kinabaluensis elucidated and transferred to Scindapsus - Kartini Saibeh; Siva Rohgini Batumale; Peter C. Boyce (Botanic Garden and Botanical Museum Berlin (BGBM), 2015)
Rhaphidophora kinabaluensis Furtado (Araceae: Monstereae), described from Sabah, Malaysian Borneo, has been recollected and revealed to be a species of Scindapsus Schott belonging to a species complex surrounding S. coriaceus Engl. The taxonomic transfer is made – S. kinabaluensis (Furtado) Kartini & P. C. Boyce, comb. nov. – and a description, colour illustrations and list of specimens are provided. Defining characteristics and current taxonomy of the Scindapsus Coriaceus Complex are summarized.